Retroperitoneal Approach for Ilioinguinal, Iliohypogastric, and Genitofemoral Neurectomies in the Treatment of Refractory Groin Pain After Inguinal Hernia Repair. Issue 4 (April 2020) - Gangopadhyay, Noopur; Pothula, Aravind; Yao, Amy; Geraghty, Patrick J.; Mackinnon, Susan E.
Abstract : Abstract: Inguinal hernia repair is one of the most commonly performed surgical procedures. Postoperative neuropathic groin pain is a potentially disabling complication and can be due to a neuroma of the ilioinguinal, iliohypogastric, and/or genitofemoral nerves. In this article, we present our operative technique—a retroperitoneal approach to the ipsilateral ilioinguinal, iliohypogastric, and genitofemoral nerves with neurectomy and proximal transposition of these nerves—for management of neuropathic pain. A retrospective review was performed of 12 of the patients who underwent this surgery at our institution. Three of 12 patients underwent a selective neurectomy, whereas 9 of 12 underwent a triple neurectomy; 3 of the 9 patients who underwent triple neurectomy also had a retroperitoneal peripheral nerve stimulator placed at the time of neurectomy. Pain visual analog scores (VASs) demonstrated significant improvement after neurectomy (preoperative pain VAS of 85 ± 11 vs postoperative pain VAS of 47 ± 32, P = 0.0027). Eight of 12 patients experienced partial or complete pain relief, whereas 4 of 12 patients had no pain relief. There were no major complications, and the minor complication rate was low for all patients and primarily related to peripheral nerve stimulator placement. This retroperitoneal approach to triple neurectomy for treatment of refractory groin pain in postoperative inguinal hernia repair patients is safe and effective for an otherwise devastating problem.